VD_FINDINFO 75/2009/PHC vom 12. Mai 2009 - VD Tribunal cantonal (2009)
TRAVAIL AU NOIR, DROIT AU SALAIRE, INDEMNITÉ DE VACANCES, CALCUL, SALAIRE | 16 ACTT-mpr, 321c CO, 323 CO, 329d CO, 342 al. 2 CO, 9 OLE, 11 RAVS